2019
DOI: 10.1002/anie.201812698
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping Lipid Biochemistry by Pushing Barriers in Structural Lipidomics

Abstract: Lipidomics is a rapidly growing field with numerous examples showing the importance of lipid molecules throughout biology. It has also shed light onto the vast and complex functions performed by many lipids that possess an immense diversity in molecular structures. Mass spectrometry (MS) is the tool of choice for analyzing lipids and has been the key catalyst driving the field forward. However, MS does not yet permit true molecular lipidomics wherein the identification and quantification of lipids having defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 78 publications
(55 reference statements)
0
61
0
Order By: Relevance
“…Lipids have become increasingly recognized as the central metabolites affecting human physiology and pathophysiology, and LIPID MAPS has recently expanded its tools, resources, data, and training as a free resource dedicated to serving the lipid research community ( 1 ). Following development of the LIPID MAPS nomenclature, classification, and structural representation system ( 2 , 3 ), an initial shorthand nomenclature was proposed ( 4 ), which included a structural hierarchy as shown by others as well ( 5 , 6 ). These were the first attempts to provide rules for reporting mass spectrometric data dependent on the power for structural resolution of lipids by the instrumental set-ups in use at that time.…”
mentioning
confidence: 99%
“…Lipids have become increasingly recognized as the central metabolites affecting human physiology and pathophysiology, and LIPID MAPS has recently expanded its tools, resources, data, and training as a free resource dedicated to serving the lipid research community ( 1 ). Following development of the LIPID MAPS nomenclature, classification, and structural representation system ( 2 , 3 ), an initial shorthand nomenclature was proposed ( 4 ), which included a structural hierarchy as shown by others as well ( 5 , 6 ). These were the first attempts to provide rules for reporting mass spectrometric data dependent on the power for structural resolution of lipids by the instrumental set-ups in use at that time.…”
mentioning
confidence: 99%
“…Thus, a standard is urgently needed. Fortunately, an effort has been initiated by Lipidomics Standards Initiative (LSI) to facilitate the standardization of lipidomics and to establish standards in all aspects of lipidomics spanning lipid analysis, pre-analytics, lipid extraction methods, MS, analysis of data, quality controls, and minimal reporting 61 .…”
Section: Implications Perspectives and Challenges Of The Aberrant Lmentioning
confidence: 99%
“…42) Standard low-energy collision-induced dissociation (CID) mass spectrometry tools can provide information at the rst three levels. However, CID o en does not reveal the more subtle structural characteristics such as sn-position and double bond position, 43,44) although it has been shown that information on the sn-position can also be achieved with CID for some lipid classes under the right conditions. 45) Recently, new approaches have been developed to tackle these limitations and allow more complete lipid structure determination, including ultraviolet photodissociation (UVPD), Paternò-Büchi (PB) reactions, ozone-induced dissociation (OzID), charge-remote fragmentation (CRF), high-eld asymmetric waveform ion mobility spectrometry (FAIMS) and meta-chloroperoxybenzoic acid (mCPBA) epoxidation.…”
Section: Lipidsmentioning
confidence: 99%